Carotid–Femoral Pulse Wave Velocity in the Prediction of Cardiovascular Events and Mortality: An Updated Systematic Review and Meta-Analysis. (August 2018) - Zhong, Qi; Hu, Ming-Jun; Cui, Yan-Jie; Liang, Ling; Zhou, Meng-Meng; Yang, Yu-Wei; Huang, Fen
Arterial stiffness (AS) is a predictor of coronary artery outcomes in patients with cardiovascular disease (CVD). Carotid–femoral pulse wave velocity (cf-PWV) is a commonly used method for assessing AS. This study aimed to assess the relationship between cf-PWV and clinical CVD events. Of the 786 studies identified, 19 studies were included in the final meta-analysis. Meta-analysis revealed that participants with high cf-PWV by 1 standard deviation (SD), 1 m/s, and cutoff points have a high pooled relative risk for CVD events (1 SD: 1.25, 95% confidence interval [CI]: 1.19-1.31; 1 m/s: 1.12, 95% CI: 1.07-1.18; and cutoff points: 1.80, 95% CI: 1.45-2.14) and CVD mortality (1 SD: 1.23, 95% CI: 1.15-1.31; 1 m/s: 1.09, 95% CI: 1.04-1.14; and cutoff points: 1.85, 95% CI: 1.46-2.24). In addition, we found that the predictive value of increased AS was higher in patients with higher disease risk for total CVD events and CVD mortality than in other patients. Carotid–femoral pulse wave velocity is a useful biomarker to improve the prediction of CV risk for patients and identify high-risk populations who may benefit from aggressive CV risk factor management.